2006
DOI: 10.1029/2006jd007090
|View full text |Cite
|
Sign up to set email alerts
|

Alaskan and Canadian forest fires exacerbate ozone pollution over Houston, Texas, on 19 and 20 July 2004

Abstract: On Monday, 19 July, and Tuesday, 20 July 2004, the air over Houston, Texas, appeared abnormally hazy. Transport model results and data from the Atmospheric Infrared Sounder (AIRS), the Moderate Resolution Imaging Spectrometer (MODIS), the Measurement of Ozone by Airbus In-service airCraft (MOZAIC) experiment, and the Total Ozone Mapping Spectrometer (TOMS) indicate that an air mass originating on 12 July 2004 over forest fires in eastern Alaska and western Canada arrived in Houston about 1 week later. Ozoneson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 34 publications
(40 reference statements)
2
86
0
Order By: Relevance
“…This may be because of over classification with the use of both primary and secondary discharge codes. However, an increase in cardiovascular and respiratory hospitalizations is consistent with the literature [8,16,24,50,66], though some literature has shown no increase in cardiovascular hospitalizations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or mortality [67]. Figure 4 displays the percent increase in hospital admissions for the haze period compared to the non-haze period in the affected region for all specific diagnoses of interest with single and distributed lag models.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This may be because of over classification with the use of both primary and secondary discharge codes. However, an increase in cardiovascular and respiratory hospitalizations is consistent with the literature [8,16,24,50,66], though some literature has shown no increase in cardiovascular hospitalizations [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] or mortality [67]. Figure 4 displays the percent increase in hospital admissions for the haze period compared to the non-haze period in the affected region for all specific diagnoses of interest with single and distributed lag models.…”
Section: Resultssupporting
confidence: 73%
“…Forest fires are known to be a major source of air pollutants [1] on a local and a global scale [2][3][4][5][6]. Each year, combustion products from local and distant wildfires impact large populations worldwide [5,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This was due primarily to regulatory measures such as the NOx State Implementation Plan (SIP) Call of 2002 (Aburn et al, 2015) that lead to regional reductions of anthropogenic NOx (nitrogen oxides), an ozone precursor (Gégo, et al, 2007), and a decline of the annual average number of exceedance days from 52 during [2000][2001][2002] Wildfires are known sources of both primary and secondary pollutants, including carbon monoxide (CO), fine particles (PM 2.5 ), NOx, volatile organic compounds (VOCs; Hu et al, 2008), and O 3 (Andreae and Merlet, 2001;McKeen et al, 2002;Bytnerowicz, et al, 2010). Similar to the study presented here, Canadian wildfires have increased O 3 concentrations in Houston, TX (Morris et al, 2006), and as far away as Europe (Spichtinger et al, 2001). Evidence of Canadian wildfire smoke and biomass burning affecting the MA's particulate matter (PM) air quality was also previously reported (Adam et al, 2004;Colarco et al, 2004;Sapkota et al, 2005), but wildfire smoke has also been recognized in high-O 3 events on the East Coast (Fiore et al, 2014).…”
Section: Introductionsupporting
confidence: 72%
“…Aircraft and ground-based measurements have shown that Asian fires can influence O 3 concentrations over North America Morris et al, 2006), the Arctic (Warnecke et al, 2008) and even Europe (Simmonds et al, 2005). For example, Bertschi and Jaffe (2005) have shown that Siberian fires have caused three ozone pollution events over the coast of Washington state in 2002.…”
Section: Introductionmentioning
confidence: 99%